Macromedia flash MX 2004 : design professional - Shuman, James E; Patel, Piyush (Boston, Mass. : Thomson/Course Technology, 2004)
Shows how to create professional looking Flash animations with Macromedia Flash MX 2004.
Getting started with Macromedia Flash -- Drawing in Macromedia Flash -- Working with symbols and interactivity -- Creating animations -- Creating special effects -- Preparing and publishing movies -- Importing and modifying graphics -- Building complex animations -- Using basic ActionScript -- Adding sounds -- Using advanced ActionScript.
Includes index.
Keywords: Flash (Computer file); Computer animation; Web sites -- Design